2022
DOI: 10.21203/rs.3.rs-2162921/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of vaccination and public awareness in forecasts of monkeypox incidence in the United Kingdom

Abstract: Since May 2022, monkeypox virus (MPXV) has spread rapidly in high-income countries through close human-to-human contact primarily amongst communities of gay, bisexual and men who have sex with men (GBMSM). Behavioural change arising from increased knowledge and health warnings may have reduced the rate of transmission and Vaccinia-based vaccination is likely to be an effective longer-term intervention. We investigate the UK epidemic presenting 26-week projections using a stochastic discrete-population transmi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…A recent modelling study which was t to weekly reported UK Monkeypox cases, required a substantial rapid change in sexual behaviour in the GBMSM and wider community in May and June 2022 to t the apparent surge and then attening of reported cases [11]. However, as noted by the authors, they did not model changes in the reporting delays, which our work now suggests was the cause of the apparent sharp drop in the growth rate around the end of May 2022.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent modelling study which was t to weekly reported UK Monkeypox cases, required a substantial rapid change in sexual behaviour in the GBMSM and wider community in May and June 2022 to t the apparent surge and then attening of reported cases [11]. However, as noted by the authors, they did not model changes in the reporting delays, which our work now suggests was the cause of the apparent sharp drop in the growth rate around the end of May 2022.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, high attack rates in dense sexual networks may also be signi cant in inhibiting the exponential growth of the virus after an early peak in transmission. Subsequent more gradual reductions in growth rate in their model were attributed to high levels of prevalence in the core GBMSM transmission group (thus gaining herd-immunity) and to a vaccine programme in this cohort [11]. Under the Joint Committee on Vaccination and Immunisation (JCVI)'s recommendation, vaccination against Monkeypox in the UK was offered to GBMSM at highest risk from June 21, 2022 [12] with the vaccination campaign speeding up from July 22, 2022 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, modeling studies have found that behavioral modifications within the queer community was the main contributing factor to the slowing mpox spread in Washington D.C., although they also found that vaccination campaigns were ultimately needed to definitively curb the local epidemic and prevent future outbreaks (43,44). Additionally, a UK-based modeling study focusing on gay and bisexual men who have sex with men found that vaccination could not explain the drop in mpox incidence in the region, but rather attribute the declining incidence to changes in behavior within the same community (45). Together, these findings highlight the significant effect of behavioral change among men who have sex with men and other high-risk communities in curbing the epidemic as well as push for a prompt public health response that includes early vaccination campaigns in order to maximize the population-level effectiveness of vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The compartmental model incorporated assumptions regarding mixing patterns between gbMSM and non-gbMSM to characterize population-level community transmission, while the ABM integrated detailed sexual contact patterns. Model results suggest that: (1) behavior change rather than vaccination was likely the main cause of the short epidemic duration, (2) in the absence of behavior change, vaccination programs can decrease the size and duration of the outbreak, and (3) continued case importation is necessary for a mpox resurgence.Similarly toBrand et al, (2023) the compartmental model highlighted the contribution of behavior changes to the evolution of the outbreak, including the short epidemic duration 30. The delayed and greater epidemic peak simulated in the uncontrolled growth scenario, compared to observed cases, suggests that the decreased transmission likely resulted from behavior.…”
mentioning
confidence: 94%